Temperament, Context and Sexual Risk among College Students. (2011) - von Sadovszky, Victoria
Abstract : Much is known about predictors of risky sexual behaviors in young adults. Little is known; however, about the contribution of temperament and how temperament interacts with context to influence sexual risk intentions and actual behaviors. Since intentions are closely linked to behavior, knowing how temperament influences these decisions is important in planning interventions. The purpose of this quasiexperimental study was to examine the effect of gender, temperament, and context on sexual risk intentions and behaviors among college students (N = 145 ). Although individual components of temperament were associated with sexual risk intentions, temperament did not predict sexual risk intentions in a safer or risky context or actual behaviors. There were also no differences by gender. In this study, temperament did not interact with context to influence sexual risk intentions or behaviors. According to these results, interventions promoting safer sexual behaviors may not have to be tailored to individuals with different temperament styles.